Apical microleakage measurement techniques in endodontics: a narrative review - Fabiani-Ticona, Ábilson Josué (2022)
Objective. To review the world literature regarding apical microleakage measurement techniques in endodontics. Methods. This is a narrative review that consists of reading and contrasting different sources through a search in the digital databases: PubMed, SciELO and Google Scholar. Twentyone articles were included in the literature review, selected according to the established inclusion criteria. Results. The following techniques were found: dye penetration fluid fltration, dye dissolution, bacteria and toxin infiltration method, air pressure method, electrochemical method, radioisotope method, metal solution tracers, inverse diffusion method, artificial cavities, scanning electron microscopy, transmission electron microscopy, computedmicrotomography. Conclusions. A perfect apical seal is desirable to prevent remaining bacteria and their endotoxins from reaching the root apex. Apical leakage is considered to be the common cause of endodontic failure and is influenced by many variables, such as variation in flling techniques, the chemical and physical properties of the various filling materials in the root canal system, and the presence or absence of the smear layer.